Can asthma control be achieved? - Grzelewska-Rzymowska, Iwona (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
International guidelines for asthma management and prevention – GINA 2006 (Global Strategy for Asthma) currently recommend low-dose ICS as a first line therapy for patients with mild persistent asthma (the second step of therapy), and medium-dose of ICS or combination therapy with LABAs as the preferred therapy for moderate asthma (the third step of therapy). Achieving asthma control is a main therapeutic goal. Although combination of ICS and LABA is generally effective pharmacotherapy, many patients fail to achieve partial or full control with available therapies. Experiments have led to the development of a fixed combination in a single inhalator (single inhalator therapy – SIT) of fluticasone/salmeterol and budesonide/formoterol. Single inhalator therapy is more convenient to use, and may also improve adherence to long-term therapy. The Gaining Optimal Asthma Control (GOAL) study assessed the impact of achieving and maintaining a guideline-defined measure for control. The treatment regimen (fluticasone vs. fluticasone/salmeterol) applied in the GOAL study facilitated the achievement of control for 70% of the patients, but 30% of patients remained uncontrolled at the end of the study. The patients treated with the combination of fluticasone/salmeterol achieved a great level of well-controlled asthma at each cumulative dose step compared to fluticasone alone. Recently a new model of asthma treatment has been proposed. Its name is SMART (single maintenance and relief therapy). In the SMART model therapy a combination of budesonide/formoterol is given twice a day and as needed. This method allows better control of asthma to be achieved. The GINA report pays attention to the importance of a close partnership between doctor and patient, self-management education and creation of a written plan in achieving asthma control.